EMPOWERING LEADERSHIP TERHADAP KINERJA PEGAWAI DAN PERILAKU KERJA PROAKTIF SEBAGAI PEMODERASI DI BADAN PENGELOLAAN PAJAK DAN RETRIBUSI DAERAH KOTA TERNATE - Sabuhari, Rahmat; Nurlaila, Nurlaila (Cakrawala Management Business Journal, 2023)
ABSTRACT The application of empowering leadership is critical in improving employee performance in a local government organization. This research aims to directly test the influence of empowering leadership and proactive work behavior on performance and the role of proactive work behavior in moderating empowering leadership on employee performance at the Tax and Levy Management Agency Ternate City Area. The method used was a structural equation model, with PLS analysis to test the hypothesis. The sample obtained was 131 ASNs who work in the Regional Government sector as research respondents. Questionnaires were delivered directly by the research team to respondents. The results of the analysis show that empowering leadership and proactive work behavior have a direct effect on employee performance. Proactive work behavior can play a role in strengthening the influence of empowering leadership on employee performance. Implementing aggressive work behavior will further enhance empowering leadership capabilities in improving the performance of Ternate City Regional Tax Retribution Management Agency employees.